ความสัมพันธ์ระหว่างสมรรถนะในตน ภาวะผู้นำการเปลี่ยนแปลง กับความสามารถในการเจรจาต่อรองของหัวหน้าหอผู้ป่วย โรงพยาบาลสังกัดกระทรวงกลาโหม - ยุพิน ยศศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study self-efficacy, tranformational leadership and the negotiation ability of head nurses, to analyze the relationships between self-efficacy, transformational leadership and negotiation ability of head nurses, hospitals under the jurisdiction of the Ministry of Defense. The study subjects consisted of 174 head nurses. Research instruments were self-efficacy, transformational leadership questionnaires, and test of negotiation ability. These questionnaires were tested for their content validity and reliability. The alpha coefficient of self-efficacy, transformational leaderships questionnaires and test of negotiation ability were .96, .96 and .71 respectively. Statistical methods used for data analysis were frequency, mean, standard deviation and Pearson s product moment correlation coefficient. Major findings were as follows 1. Mean score of self-efficacy of head nurses in hospitals under the jurisdiction of the Ministry of Defense was at the high level (4.03) 2. Mean score of transformational leadership of head nurses in hospitals under the jurisdiction of the Ministry of Defense was at the high level ( 4.35) 3. Mean score of the negotiation ability of head nurses in hospitals under the jurisdiction of the Ministry of Defense was at the moderated level (3.91) 4. Self-efficacy and transformational leadership were not significantly related to negotiation ability of head nurses in hospitals under the jurisdiction of the Ministry of Defense.